(untitled) (Medical Forum Monthly, 2024)
Objective: The aim of this study was to compare the effect of both add-on therapies; Salmeterol plus Inhaled Corticosteroid and Montelukast and Inhaled Corticosteroid on asthma control in poorly controlled asthma. Study Design: Randomized clinical trial. Place and Duration of Study: Department of Pharmacology and Therapeutics, Basic Medical Sciences Institute, Jinnah Post-graduate Medical Centre, Karachi from December 2007 to June 2008. Materials and Methods: 75 patients aged between 15-65 years, suffering from mild to moderate asthma were randomly divided in three groups. Group A was given Salmeterol 50µg and Fluticasone propionate 250µg twice daily, Group B was given tablet Montelukast 10mg at night in addition to Beclomethasone Dipropionate 500µg twice daily and Group C was given Beclomethasone Dipropionate 500µg twice daily. Improvements in Peak Expiratory Flow Rate (PEFR) and FEV1 were assessed by Peak Expiratory Flow Meter and Spirometry, fortnightly at the beginning and end of treatment respectively. Student paired t test was applied to analyze data. Results: An improvement of 46.58 %( P-value <0.001), 38.59% (P-value <0.005) and 21.2% (P-value not significant) in PEFR was noted in Group A, B and C respectively. In Group A and B FEV1 increased from1.17L/min (±0.12) to 1.41L/min (±0.13), and 1.42L/min (±0.13) to 1.62L/min (±0.13) respectively, while in Group C it was from 1.24L/min (±0.12) to 1.26L/min (±0.13). Conclusion: Salmeterol is slightly more effective than Montelukast as add-on treatment in increasing PEFR in patients suffering from mild to moderate persistent asthma.